Features of physical training skiers sprinters - Golovko D. E. (Новое слово в науке: перспективы развития, 2016)
with the advent of skiing sprints, there was the need for training sprinters skiers. We must look for new methods and means for the preparation of skiers is to sprint. It requires improving the training process.
Keywords: физическая подготовка; тренировочный процесс; physical training; the training process; лыжный спринт; ski sprint